ChemInform Abstract: A New and Versatile Synthesis of 3‐Substituted Oxetan‐3‐yl Methyl Alcohols. Issue 51 (23rd December 2014) - Boyd, Scott; Davies, Christopher D.
Abstract The synthesis of pharmaceutically significant title compounds from readily available malonates allows access to a range of oxetanes.